Self-exploration, anonymity and risks in the online setting – analysis of narratives by 14-18-year olds - Keipi Teo; Oksanen Atte (Routledge, 2022)
This article explores youth narratives of internet risks and opportunities brought about by user anonymity. Using an essay-based study of 258 youth (mean age 15.4 years, 56% female), we examined youth narratives concerning the effects of internet anonymity on youth behavior online. Narratives were written anonymously to maximize disclosure. The needs categories of Self-Determination Theory (SDT) for autonomy, relatedness, and competence were used to identify risks and opportunities in youth narratives. The analysis of the data was thematic, using both quantitative and qualitative methods with SDT providing an effective descriptive framework. Quantitative thematic analysis showed that 17% of the narratives included a notion of competence, 32% autonomy and 30% relatedness. Risks were also prevalent in the narratives, with primary themes of 74% cyberbullying and insults, 27% identity theft and risky false identity, and 18% sexual harassment or exploitation. The qualitative analysis underlines the interaction of both risks and opportunities in the use of social media online by youth. These findings illuminate both the importance of Internet opportunities as a social tool for youth need fulfillment toward self-determination and the social risks that youth internet use involves.